Genetic analysis of 50 Y-STR loci in Dong, Miao, Tujia, and Yao populations from Hunan - Feng, Rui; Zhao, Yang; Chen, Shuiqin; Li, Qiong; Fu, Yong; Zhao, Lin; Zhou, Yongsong; Zhang, Lei; Mei, Xinglin; Shi, Minghao; Yin, Jianying (International journal of legal medicine, 2020)
To investigate the genetic polymorphism of Y chromosome short tandem repeat (Y-STR) loci in Dong, Miao, Tujia, and Yao minority populations from Hunan Province, China. Fifty Y-STRs (DYS392, DYS389I/II, DYS447, DYS438, DYS527, DYS645, DYS596, DYS391, DYS456, DYS19, DYS593, DYS448, DYS627, DYS557, DYS437, DYS481, DYS533, DYS390, DYS385, DYF387S1, DYS460, DYS393, Y_GATA_H4, DYS439, DYS635, DYS444, DYS643, DYS549, DYS576, DYS570, DYS458, DYS449, DYS518, DYS531, DYS630, DYS622, DYS552, DYS510, DYS459a/b, DYS446, DYS443, DYS587, Y_GATA_A10, DYS520, DYS522) were analyzed for 2553 unrelated healthy male individuals from Hunan (643 Dong males, 666 Miao males, 633 Tujia males, 611 Yao males) using AGCU Y37 and AGCU Y SUPP STR amplification system. There were 624 different haplotypes in 643 unrelated Dong males, 662 in 666 unrelated Miao males, 627 in 633 unrelated Tujia males, and 587 in 611 unrelated Yao males. The haplotype diversities of Dong, Miao, Tujia, and Yao were determined as 0.999879, 0.999982, 0.999970, and 0.999860, respectively. Analysis of molecular variance (AMOVA) tests demonstrated that genetic distance between Miao and Tujia was the smallest (0.0003), while the genetic distance between Dong and Yao was the largest (0.0252). The 50 Y-STR loci in the four minority populations from Hunan Province revealed a highly polymorphic genetic distribution, which showed a high potential for population genetics and forensic practice.